Pertumbuhan dan Perawakan Pendek - Aditiawati (Conferences of Medical Sciences Dies Natalis, 2019)
Growth that is reflected by height can vary between races, sexes, and ages. Impaired growth of children can occur during the growth process that takes place from intra uterine to adulthood. Impaired growth of children such as short stature and high stature, both caused by endocrine and non-endocrine disorders is a disorder that is often found. Careful clinical examination is needed which is supported by endocrinological examination to look for etiology. Bone age examination is an important radiological examination for growth evaluation. Various attempts were made to optimize the management of children with short stature. Children with normal variations in short stature usually do not need treatment, whereas children with pathological disorders require treatment according to etiology.